2015
DOI: 10.1096/fj.15-279885
|View full text |Cite
|
Sign up to set email alerts
|

C1q/TNF‐related protein‐1 functions to protect against acute ischemic injury in the heart

Abstract: Obesity is associated with an increased risk of cardiovascular disease. C1q/TNF-related protein (CTRP)-1 is a poorly characterized adipokine that is up-regulated in association with ischemic heart disease. We investigated the role of CTRP1 in myocardial ischemia injury. CTRP1-knockout mice showed increased myocardial infarct size, cardiomyocyte apoptosis, and proinflammatory gene expression after I/R compared with wild-type (WT) mice. In contrast, systemic delivery of CTRP1 attenuated myocardial damage after I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 44 publications
1
51
0
Order By: Relevance
“…Some previous reports have suggested that the CTRP1 levels were increased in patients with stable coronary heart disease and mice with acute ischaemic injury [20, 21]. In this study, we excluded patients with acute myocardial infarction and found dynamic changes in the plasma concentration of CTRP1 in CHF patients.…”
Section: Discussionmentioning
confidence: 79%
“…Some previous reports have suggested that the CTRP1 levels were increased in patients with stable coronary heart disease and mice with acute ischaemic injury [20, 21]. In this study, we excluded patients with acute myocardial infarction and found dynamic changes in the plasma concentration of CTRP1 in CHF patients.…”
Section: Discussionmentioning
confidence: 79%
“…In 2004, Wong et al characterized a novel family of adipose tissue-derived cytokines, collectively called adipokines, referred to as Complement C 1q T umor necrosis factor- R elated P roteins (CTRPs) (76), like adiponectin and tumor necrosis factor (TNF) these CTRPs all contain a C1q globular domain and are characterized together as the C1q/TNF superfamily (62). To date, this superfamily has been documented to have a wide range and opposing effects on metabolism, food intake, inflammation, tumor metastasis, apoptosis, vascular disorders, ischemic injury, and even sexual reproduction (7, 8, 25, 29, 30, 49, 51, 57, 62, 64, 68, 69, 74-76, 81, 84, 89). The purpose of this review is to carefully summarize the research that has been accomplished on one of these proteins, CTRP3.…”
Section: Introductionmentioning
confidence: 99%
“…(21,22) Although there is evidence on the protective role of CTRP1 in murine heart injuries, the exact role of CTRP1 in these conditions is still not fully understood and requires further studies. (23) CTRP5, another member of CTRPs family also expressed in a wide range of tissues including adipose tissue, eye, testis, skeletal muscle, brain, spleen, uterus, and ciliary epithelium but like CTRP1, adipose tissue is considered as the main secretor. (21) CTRP5 increases glucose uptake via stimulating plasma membrane incorporation of the glucose transporter 4 (GLUT4) into plasma membrane by a mechanism dependent on AMPK phosphorylation.…”
Section: Discussionmentioning
confidence: 99%